2023
DOI: 10.1111/hex.13862
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and acceptance of malaria vaccine among parents of under‐five children of malaria endemic areas in Bangladesh: A cross‐sectional study

Mohammad Ashraful Amin,
Sadia Afrin,
Atia S. Bonna
et al.

Abstract: BackgroundMalaria exists as an endemic in many countries including Bangladesh and the malaria vaccine is not yet available here. The study aimed to assess the level of knowledge and acceptance of the malaria vaccination among the parents of children under the age of five in Bangladesh's malaria‐endemic areas and the sociodemographic, behavioural, and household factors associated with the acceptance and knowledge of the malaria vaccine.MethodsFrom January to March 2022, a cross‐sectional study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…EPI has proven effective in immunization coverage. A study in Bangladesh for instance, has indicated the significant impact of the EPI programme in the country's high coverage rates for infants and children immunization, which led to a significant reduction in child mortality rates [31]. Although the EPI programme is currently in operation…”
Section: Discussionmentioning
confidence: 99%
“…EPI has proven effective in immunization coverage. A study in Bangladesh for instance, has indicated the significant impact of the EPI programme in the country's high coverage rates for infants and children immunization, which led to a significant reduction in child mortality rates [31]. Although the EPI programme is currently in operation…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance rates of the malaria vaccine varied across different studies: from 32.3% in an Ethiopian study conducted by Asmare [ 21 ], to 70% in a study by Amin et al . in Bangladesh [ 22 ], 84.2% in a study by Mtenga et al . in Tanzania [ 23 ] and the a high acceptance at 95.3% was reported in a meta-analysis of 11 studies conducted in 5 low and middle income countries by Sulaiman et al .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies were published in the African Region. There were seven studies from Nigeria [5][6][7][8][9][10][11], three from Ghana [12][13][14], two from Tanzania [15,16], and six from other countries [17][18][19][20][21][22]. The sample population exhibited diversity, encompassing a range of individuals from single mothers to the general public.…”
Section: Characteristics Of Studies Included In This Reviewmentioning
confidence: 99%